The effect of Fordyce happiness training on marital satisfaction and mental health in women with premenstrual syndrome - Fereshteh Abdolrahmi; Marzieh Kaboudi; Hamid Kamerzarin; Bijan Kaboudi; Parastoo Mohammadi; Mozhdeh Horriat (Journal of Holistic Nursing and Midwifery)
Introduction: Premenstrual syndrome has several physical and psychological complications. Since healthy family relationships and normal marital interactions are affected by a woman's physical and mental health, any disorder in this area decreases marital satisfaction and consequently endangers the mental health and survival of the family. Objective: This study aimed to determine the effect of Fordyce happiness training on marital satisfaction and mental health in women with premenstrual syndrome. Materials and Methods: This randomized controlled trial was performed in 2018-2019. A total of 40 women with the premenstrual syndrome were selected by convenience sampling and randomly divided into experimental (n=20) and control (n=20) groups. The experimental group received six sessions of the Fordyce happiness training program at weekly intervals in groups of 10. In both groups, the level of marital satisfaction and mental health was measured by Enriching and Nurturing Relationship Issues‚ Communication‚ and Happiness (ENRICH) marital satisfaction questionnaire, and the Goldberg Mental Health questionnaire three times: before, immediately after, and 45 days after the training sessions. The Chi-square test, Fisher exact test, independent t test, and repeated measures analysis of variance were conducted to analyze the obtained data. Results: The Mean±SD ages of the experimental and control groups were 32.45±7.33 and 33.10±6.25 years, respectively. The mean scores of mental health in the experimental group compared to the control group in the pretest, post-test, and follow-up (43.95±4.38, 41.20±5.73, 40.25±5.88) had a decreasing trend (P<0.05) but the mean scores of marital satisfactions in the experimental group (81.90±7.18, 86.35±8.16, 86.80±7.96, respectively) increased (P<0.05). However, no significant change was observed in the control group. Time significantly affects the mean changes in mental health (P=0.002) and marital satisfaction (P=0.001) in the samples. The time-group effect also shows a significant change for both variables (partial eta-squared for mental health=0.174 and marital satisfaction=0.165); the changes in the mean mental health and marital satisfaction of the research samples over time are different between the experimental and control groups; there are changes in the mean score of the two variables in three time points. Conclusion: The findings of the present study showed that Fordyce happiness training is effective in improving the level of marital satisfaction and mental health of women with premenstrual syndrome. Therefore, it is suggested that this training program is used to adapt women psychologically to the mood and physical changes of premenstrual syndrome.